Vers de nouvelles formes générationnelles d’engagement au Parti travailliste britannique ? - Nicolas Jara-Joly; Denis Rayer (Revue LISA)
Between 2015 and 2020, the Labour Party, a traditional social-democratic political party led at the time by Jeremy Corbyn, an uncharismatic man in his late sixties, benefitted from a high level of popularity among young people in Britain. This initially counter-intuitive phenomenon has been linked in the existing literature to the Party manifesto, new campaigning methods and Corbyn’s personality traits. However, few studies have sought to analyse the practices of young activists themselves and the way in which they attempted to influence the renewal of political activism within Labour. This article explores this question through the lens of the festival The World Transformed, a space of mobilization, participation and sociability created by young activists themselves as a linkage between social movement and party activism. It brings into relief the forms of hybrid engagement which characterise the political uses of this festival.